Spatio-temporal changes in vegetation net primary productivity and its responses to climatic factors in Jiangsu Province, Eastern China - Li, Cheng; Wang, Ranghui; Tan, Mou Leong (Penerbit Universiti Kebangsaan Malaysia, 2019)
Vegetation net primary productivity (NPP) is an important indicator in determining the ecological functions and carbon cycle of terrestrial ecosystems. As an important part of Chinese Yangtze River Delta region, Jiangsu is one of main grain producing areas in China. Therefore, understanding of spatio-temporal changes in NPP has a practical significance to ensure ecological sustainability in this region. In this study, we used satellite-based vegetation productivity model, the Carnegie-Ames-Stanford Approach (CASA) to assess spatio-temporal variations in NPP and analyzed the relationships between NPP and climatic factors over Jiangsu. The results showed that annual mean NPP reached up to 745.26 ± 69.21 g C m-2 year-1, with high NPP values mainly in the central and southwestern regions. Besides that, annual mean NPP increased from 2000 to 2015, with a rate of 6.54 g C m-2 year-1. The increasing trends with higher changing rate were mainly found in the northern regions of Jiangsu, whereas the decreasing trends were mainly found in central and southern Jiangsu. Moreover, the correlation analysis indicated that the mean temperature and total precipitation in spring had a significant relationship with the corresponding NPP in most part of Jiangsu. The findings will have an important significance for improving the ecosystem management in Jiangsu.